The proliferation of low-cost private schools: a new challenge to the enjoyment of the right to free education in Nigeria (2017)
During the past decades, low cost private school phenomenon has gained popularity and increased visibility in Nigeria. These private schools are competing with free public schools run by the government. They are profit oriented enterprises, and claiming to be making quality education available to millions of children who would have been out of school as a result of costs. The resulting effect of this influx is, private education flourishing as an attractive business with minimal control and supervision by the government. This has negative impact as it undermines the right to education. Capitalising on the inability of governments to cope with rising demands on public learning, private education providers are mushrooming, which is an indictment on the government for its failure to meet its Obligation to provide universal free and quality primary education for all its children. It is this unfortunate reality that this paper seeks to bring to light. It then concludes that the low-cost schools are no more than profiteering ventures disguised as philanthropy. Their proliferation is an assault on the very essence of public education and education as a human right